Искусcтвенная нейронная сеть как способ изучения эволюции и генетики - Дойлидов, С. В. (БНТУ, 2021)
The introduction of artificial neural network technology has been reflected in modern society. Today, you can find unmanned vehicles on the streets of cities, and computer programs have been developed that independently determine what (or who) is depicted in the picture. In connection with the above, we set the task to learn new things for the study of such branches as evolution and genetics.